Neutrophil Interactions with Epithelial Expressed ICAM-1 Enhances Intestinal Mucosal Wound Healing - Sumagin, R (Mucosal Immunol, 2016)
A characteristic feature of gastrointestinal tract inflammatory disorders, such as inflammatory bowel disease, is polymorphonuclear neutrophil (PMN) transepithelial migration (TEM) and accumulation in the gut lumen. PMN accumulation within the intestinal mucosa contributes to tissue injury. While epithelial infiltration by large numbers of PMNs results in mucosal injury, we found that PMN interactions with luminal epithelial membrane receptors may also play a role in wound healing. Intercellular adhesion molecule-1 (ICAM-1) is a PMN ligand that is upregulated on apical surfaces of intestinal epithelial cells under inflammatory conditions. In our study, increased expression of ICAM-1 resulted in enhanced PMN binding to the apical epithelium, which was associated with reduced PMN apoptosis. Following TEM, PMN adhesion to ICAM-1 resulted in activation of Akt and β-catenin signaling, increased epithelial-cell proliferation, and wound healing. Such responses were ICAM-1 dependent as engagement of epithelial ICAM-1 by antibody-mediated cross-linking yielded similar results. Furthermore, using an in-vivo biopsy-based, colonic-mucosal-injury model, we demonstrated epithelial ICAM-1 plays an important role in activation of epithelial Akt and β-catenin signaling and wound healing. These findings suggest that post-migrated PMNs within the intestinal lumen can regulate epithelial homeostasis, thereby identifying ICAM-1 as a potential therapeutic target for promoting mucosal wound healing.